2022
DOI: 10.3389/fcvm.2022.856749
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Adaptation to Prolonged High Altitude Migration Assessed by Speckle Tracking Echocardiography

Abstract: ObjectiveExposure to high altitudes represents physiological stress that leads to significant changes in cardiovascular properties. However, long-term cardiovascular adaptions to high altitude migration of lowlanders have not been described. Accordingly, we measured changes in cardiovascular properties following prolonged hypoxic exposure in acclimatized Han migrants and Tibetans.MethodsEchocardiographic features of recently adapted Han migrant (3–12 months, n = 64) and highly adapted Han migrant (5–10 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Our longitudinal study observed decreases in RV dimensional parameters one month and one year after HA exposure in healthy lowlanders, mirroring changes in the other three chambers. While LV and LA responses aligned with previous reports, the RA response differed unexpectedly, exhibiting a decrease unlike observations in earlier studies [14,18].…”
Section: Cardiac Remodelingsupporting
confidence: 89%
See 2 more Smart Citations
“…Our longitudinal study observed decreases in RV dimensional parameters one month and one year after HA exposure in healthy lowlanders, mirroring changes in the other three chambers. While LV and LA responses aligned with previous reports, the RA response differed unexpectedly, exhibiting a decrease unlike observations in earlier studies [14,18].…”
Section: Cardiac Remodelingsupporting
confidence: 89%
“…Over the years, studies examining RV area in healthy lowlanders upon initial HA exposure have yielded inconsistent results, reporting slight increases [16], no changes[6, 17], or decreases after prolonged acclimatization (after more than 5 years) [14]. Additionally, RV dimensions vary across populations at different altitudes: lower in Himalayan Sherpa (5050 m) [17], higher in Peruvian Andeans at La Rinconada (5100 m)[18], similar to lowlanders in Tibetans (4300 m) [14] and Peruvian Andeans at Puno (3800 m) [18]. These discrepancies potentially arise from differences in age, ethnicity, and exposure time among crosssectional study participants.…”
Section: Cardiac Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, insight into the broad scope of molecular mechanisms that govern cardiac plasticity remains limited. There are several notable examples of robust, reversible cardiac remodeling occurring in vertebrates including in fish with thermal acclimation [1][2][3][4] , birds flying at high altitudes [5][6][7] , and pythons following consumption of large prey [8][9][10][11][12] . Such unconventional model organisms represent unique platforms in which to discover the molecular biology underlying cardiac plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…The myocardial high oxygen consumption rate makes it sensitive to hypoxia. While a series of physiological adaptations of the cardiovascular system enable the organs to better cope with increased oxygen demand, the chronic HH conditions can still impair the myocardium (Jing et al 2020 ; Chen et al 2022 ). Therefore, understanding the biochemical mechanisms underlying chronic HH-induced myocardial impairment and exploring the therapeutic method has been a focus of research in high-altitude medicine.…”
Section: Introductionmentioning
confidence: 99%